Qualitative Research in Information Systems 2002
DOI: 10.4135/9781849209687.n11
|View full text |Cite
|
Sign up to set email alerts
|

CASE Tools as Organizational Change: Investigating Incremental and Radical Changes in Systems Development

Abstract: This paper presents the findings of an empirical study into two organizations' experiences with the adoption and use of CASE tools over time. Using a grounded theory research approach, the study characterizes the organizations' experiences in terms of processes of incremental or radical organizational change. These findings are used to develop a theoretical framework for conceptualizing the organizational issues around the adoption and use of these tools--issues that have been largely missing from contemporary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 18 publications
2
116
0
5
Order By: Relevance
“…For example, when new technology requires a new way to coordinate actions across individuals, it is difficult to describe the knowledge needed for improvement. This know-how is rooted in action, and is improvisational (Orlikowski, 1993). Researchers thus emphasize the contextually embedded nature of knowledge about technology use in organizations (Orlikowski, 2000;Von Hippel & Tyre, 1995).…”
Section: Tacit Versus Codifiedmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, when new technology requires a new way to coordinate actions across individuals, it is difficult to describe the knowledge needed for improvement. This know-how is rooted in action, and is improvisational (Orlikowski, 1993). Researchers thus emphasize the contextually embedded nature of knowledge about technology use in organizations (Orlikowski, 2000;Von Hippel & Tyre, 1995).…”
Section: Tacit Versus Codifiedmentioning
confidence: 99%
“…Research on team and organizational learning has demonstrated substantial variance in experimentation or trial-and-error learning processes across groups (Edmondson, 1999(Edmondson, , 2002 and organizations. The collective learning processes through which new know-how and tacit knowledge are developed in organizations are fraught with uncertainty and difficult to reproduce (Orlikowski, 1993). Stable membership thus promotes rapid performance improvement when learning a new group task (Moreland, 1999).…”
Section: Transfer Versus Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a qualitative approach that has been has been variously described as positivist, interpretive or critical (Urquhart et al, 2010). Grounded theory has been used in the IS field; Orlikowski (1993), for example in investigating the use of Computer Aided Software Engineering tools in organizations. Matavire and Brown (2008) have identified four main grounded theory approaches in IS research.…”
Section: Methodsologymentioning
confidence: 99%
“…Certainly, the mixed findings of extant research on CASE adoption and use support this argument. Much of this research has been survey based and falls prey to criticisms such as those levelled at similar research conducted on other aspects of systems development (for examples, see Markus & Robey, 1988;Orlikowski, 1993;Cavaye, 1995). Qualitative interpretive research approaches are therefore indicated as appropriate to capture the 'rich picture' of systems development in organizations (Cavaye, 1995;Myers, 1995;cf.…”
mentioning
confidence: 99%